(untitled) (Research, Society and Development, 2021)
Objective: to describe the planning strategies and the development of remote education on the nursing process in the COVID-19 Pandemic. Method: this is an experience report about the remote teaching strategies undertaken in the discipline of Fundamentals of Nursing III on the Nursing Process with data collection period from July to November 2020. The analysis performed was of the descriptive type. Results: interactivity in remote education was essential for the continuous planning of the virtual environment through the use of tools and applications in the face of the social isolation imposed by Pandemia. Final considerations: the possibility of seeking interactivity in remote education in the following aspects: continuous planning; the teacher as the one who mediates knowledge; combining the virtual learning environment with the current needs of remote education.